High [CO2] and Temperature Increase Resistance to Cyhalofop-Butyl in Multiple-Resistant Echinochloa colona - Refatti, João Paulo; de Avila, Luis Antonio; Camargo, Edinalvo Rabaioli; Ziska, Lewis Hans; Oliveira, Claudia; Salas-Perez, Reiofeli; Rouse, Christopher Edward; Roma-Burgos, Nilda (Frontiers in Plant Science, 2019)
Changes in the environment, specifically rising temperature and increasing atmospheric carbon dioxide concentration [CO2], can alter the growth and physiology of weedy plants. These changes could, potentially, alter herbicide efficacy, crop-weed interaction, and weed management. The objectives of the current research were to quantify the effects of increased atmospheric [CO2] and temperature on absorption, translocation and efficacy of cyhalofop-butyl on multiple-resistant (MR) and susceptible (S) Echinochloa colona genotypes. E. colona, or junglerice, is a troublesome weed in rice and in agronomic and horticultural crops worldwide. Cyhalofop-butyl is a grass herbicide that selectively controls Echinochloa spp. in rice. Maximum 14C-cyhalofop-butyl absorption occurred at 120 h after herbicide treatment with >97% of cyhalofop-butyl retained in the treated leaf regardless of [CO2], temperature, or genotype. Neither temperature nor [CO2] affected herbicide absorption into the leaf. The translocation of herbicide was slightly reduced in the MR plants vs. S plants either under elevated [CO2] or high temperature. Although plants grown under high [CO2] or high temperature were taller than those in ambient conditions, neither high [CO2] nor high temperature reduced the herbicide efficacy on susceptible plants. However, herbicide efficacy was reduced on MR plants grown under high [CO2] or high temperature about 50% compared to MR plants at ambient conditions. High [CO2] and high temperature increased the resistance level of MR E. colona to cyhalofop-butyl. To mitigate rapid resistance evolution under a changing climate, weed management practitioners must implement measures to reduce the herbicide selection pressure. These measures include reduction of weed population size through reduction of the soil seedbank, ensuring complete control of current infestations with multiple herbicide modes of action in mixture and in sequence, augmenting herbicides with mechanical control where possible, rotation with weed-competitive crops, use of weed-competitive cultivars, use of weed-suppressive cover crops, and other practices recommended for integrated weed management.